PENGARUH DISIPLIN KERJA TERHADAP KINERJA PERANGKAT DESA PADA KANTOR DESA BANGSA NEGARA KECAMATAN BELITANG MADANG RAYA KABUPATEN OKU TIMUR - Rofiatin, Ummi; Sarwo Sari, Sri (JMBI (Journal of Marketing and Business Intelligence), 2024)
This research is a quantitative research using a survey method with a data collection technique using a questionnaire by distributing questionnaires to village officials. Sampling using a total sampling technique, namely all Bangsa Negara village officials totaling 12 people. The results of this study indicate that work discipline has a positive and significant influence on the performance of village officials. Based on the simple linear regression equation is Y = 2,094 + 0.884, and the correlation value of 0.973 is in the position of 0.800-1,000, it is stated that the relationship is very strong. At the same time, the R square number (determination coefficient) of 0.947 indicates that the contribution of the work discipline variable, and the performance of Bangsa Negara village officials (Y) is 94.7%. At the same time, the rest is influenced by other variables not examined in this study. Based on the data obtained t count The work discipline variable obtained a t count value of 13,420 where the t count value is more than the t table value (13,420> 1,812). So there is an influence between the work discipline variable (X) on the performance of village officials (Y).